Analysis of Obstacles on Limited Face-To-Face Learning During The Covid-19 Pandemic Junior High School In Medan - Octavia, Sherly Christina; Sihombing, Rizky Agassy; Destine, Kezia Thessa; Hutagalung, Jennie Febrina (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
This study aims to describe the obstacles experienced by students during limited face-to-face learning. By making class VII-8 at Junior High School 27 Medan as a research sample, it will analyze what obstacles are experienced by students. Research method used is descriptive quantitative method. The study used an instrument in the form of a questionnaire that would be given to students directly and provided four answer choices based on a Likert scale and structured interviews. The results of the study, it was found that students experienced problems in implementing limited face-to-face learning in the four aspects, namely in the aspects of facilities and infrastructure to support learning was obtained in the fairly good category, the classroom management aspect obtained the good category, the aspect of student activity get the unfavorable category, the aspect of student understanding gets the poor category, and the aspect of student concentration in doing learning gets a poor category. For this reason, good management is still needed in overcoming several obstacles in the limited face-to-face learning process, all parties, both principals, teachers, students and other school residents must participate in overcoming the obstacles that arise.